Effects of mixing and conjugation process with pea protein isolate on functional properties of pectin in emulsions - Tamnak, Sahar (2015)
Although pectin considered as a heteropolysaccharide gum, which is used as a gelling agent, thickening agent, and stabilizer in many food products. However, it cannot be used as a proper emulsifier due to the lack of hydrophobic moieties and thus having lower tendency to adsorb at the oil droplets surface. The main goal of this study was to improve the emulsifying activity of pectin in both single and double emulsions. A full factorial design was applied to investigate the effects of pectin to protein ratio (i.e. 1:1, 2:1, 3:1, 1:2 and 1:0 w/w) and conjugation time (i.e. 0, 6, 27 and 48 h) on the functional properties of pectin. In this study, pea protein isolate was selected for the conjugation with pectin. It was hypothesized that the mixing and/or conjugation of pectin (with the hydrophilic structure) and pea protein isolate (with the hydrophobic structure) could result in the formation of a hybrid polymer with the amphiphilic structure. It could provide stronger emulsifying properties than the native pectin or pea protein isolate only. The most desirable conjugation condition was chosen after testing different conjugated hybrid polymers. Therefore, all mixed and conjugated hybrid polymers were subjected to various physicochemical tests. The main analytical assays were solubility, moisture content, morphology, sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), apparent viscosity, emulsion stability, Z-potential and average particles size and distribution. In this study, functional properties of different mixed and conjugated polymers were compared to native pectin as a control. After one-month storage of single emulsions at 4 °C, a sample containing conjugated polymer (ratio 3:1) had the highest stability (83.33%) and smallest droplets size (D [3, 2], 0.287 µm). Further, all single emulsions stabilized with mixed and conjugated pectin-protein polymers had higher Z-potential ranging from ‒33.57 to ‒49.97 mV than the samples containing native pectin (‒26.97 mV). This confirmed that both mixing and conjugation of pectin with pea protein isolate let to improve its interfacial emulsifying activity. During conjugation, the long incubation (48 h) resulted in a strong covalent linkage between pectin and pea protein isolate, thereby making a hybrid polymer with lower solubility than pectin. The results showed that the conjugated polymer (3:1), which was incubated for 48 h at 60 °C, provided the most desirable functional properties among all single, mixed and conjugated polymers. Therefore, this compound was selected as the most desirable polymer for further comparison study. Finally, the application of conjugated polymer (pectin: protein, 3:1) as a replacer for Tween 80 in the water-in-oil-in-water double emulsion was investigated. Therefore, the efficiency of different concentrations (i.e. 0.5%, 1% and 2% w/w) of the target emulsifiers with high hydrophilic-lipophilic balance (HLB) (i.e. Tween 80, native pectin and conjugated pectin) on the stability and characteristics of double (W1/O/W2) emulsions was tested. On the other hand, the effect of different concentrations (i.e. 2% and 5% w/w) of a low HLB emulsifier (i.e. Polyglycerol polyricinoleate, PGPR) on stability and release rate of the marker from different double (W1/O/W2) emulsions was investigated. In fact, encapsulation capability of various emulsifiers was compared by measuring release content of marker (i.e. edible dye Tartrazine) from the inner aqueous phase (W1) to the outer aqueous phase (W2) of the double emulsion. The current study revealed that all single (O/W) and double (W1/O/W2) emulsions exhibited a non-Newtonian pseudoplastic flow behavior. Samples containing mixed pectin-pea protein isolate and native pectin showed the highest apparent viscosity (~6 mPa.s at a medium shear rate of 60 s-1) among all prepared single emulsions. The present study showed that the double emulsions containing 2% conjugated pectin and 2% PGPR had proper encapsulation efficiency (81.26%) and encapsulation stability (37.05%). The fresh double emulsion stabilized with conjugated pectin had smaller droplets size (D [3, 2], 0.345-1.526 µm) than the other double emulsions containing native pectin (D [3, 2], 2.546-5.368 µm) and Tween 80 (D [3, 2], 1.480-1.642 µm). The present study revealed that the conjugated pectinpea protein isolate at ratio 3:1 could be used as a proper replacer for Tween 80 in stabilizing double (W1/O/W2) emulsions. The single emulsions prepared in this study may be exploited in the food industry as a suitable replacement of traditional soybean-stabilized food emulsions, especially in the manufacture of hypoallergenic foods for people allergic to soybean proteins as well as in smoothies, infant formulas, fruit juices, yogurt drinks. The double emulsions produced in this study can have several food applications such as in the formulation of reduced fat-food products (by replacing some of the volumes of the oil droplets with entrapped water drops) and as vehicles for encapsulation and delivery of hydrophilic nutrients. For example to fortify foods with water-soluble vitamins or minerals. Besides, in order to improve the fat content of meat (in quantitative and qualitative terms) fat globules can be replaced by a double (W1/O/W2) emulsion prepared by different oils having healthy effects (as lipid phase).